MANJALANG JANJANG DALAM PERSPEKTIF HUKUM ISLAM (Studi Kasus di Nagari Batu Payuang Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota) - Faida Syukrina; Zulkifli Zulkifli; Amri Effendi (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
This study examines manjalang janjang in Nagari Batu Payuang, Lareh Sago Halaban District, Lima Puluh Kota Regency. Manjalang Janjang is done after the marriage in Nagari Batu Payuang. This study wants to see how the process of implementing the majalang janjang tradition in Nagari Batu Payuang, Lareh Sago Halaban District, Lima Puluh Kota Regency and how Islamic law reviews the implementation of the majalang janjang tradition. This research is a field research. Data were obtained through interviews with tribal niniak mamak or also called datuak and married couples who did not carry out and who carried out the manjalang janjang tradition. This study found that the implementation of the manjalang janjang tradition in Nagari Batu Payuang, Lareh Sago Halaban District, Lima Puluh Kota Regency is to establish friendship and respect for the family. The purpose of the jalang janjang tradition is to respect the male side as urang sumando. According to the view of Islamic law, the tradition of manjalang janjang in Nagari Batu Payuang, Lareh Sago Halaban District, Lima Puluh Kota Regency is in the category of something good even though it is not explicitly governed. This category includes maslahah.